A novel design of multi-stable metastructures for energy dissipation - Yong Zhang (Elsevier, 2021)
Multi-stable metastructures composed of curved beams can switch to a series of stable configurations via elastic snap-through transitions. The elastic deformations allow metastructures to function as reusable energy absorbers. However, conventional metastructure designs based on solid beams often result in relatively low energy dissipation. In this work, it is found that by increasing the beam unit’s bending stiffness while keeping the volume/mass constant, energy dissipation of the metastructure can be largely improved. Based on this observation, we propose two types of structural designs (lattice and hollow cross-section design) as building blocks for multi-stable metastructures. The lattice design is realized by incorporating lattice structures into pre-shaped beams while for the hollow cross-section design, a box-shaped cross section is adopted. The proposed structures are experimentally characterized under cyclic loading and are shown to exhibit sequential snap-through transitions with relatively large energy dissipation. Results show the snap-through behavior can be further tailored through tuning structural in-plane thickness. Effects of geometric parameters on snap-through, local buckling and bi-stability are investigated, and the feasible design domains for selecting proper lattice and cross-section geometries are identified. In addition, we demonstrate that the proposed design is not restricted to beams, and can be extended to shell structures.